Exploring the Applications of Artificial Intelligence in Marketing - Rita, Paulo (2025)
Rita, P., Omran, W., Ramos, R. F., & Costa, T. (2025). Exploring the Applications of Artificial Intelligence in Marketing: A Topic Modelling Analysis. Tourism & Management Studies, 21(1), 39-55. https://doi.org/10.18089/tms.20250103 --- Paulo Rita was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project -UIDB/04152/2020 -Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS) (https://doi.org/10.54499/UIDB/04152/2020)